The vicious circles of development through dependence. An interpretation of the Romanian nineteenth century economy - Dan Velicu (CES Working Papers, 2018)
In the last decades, the academic debate on the origins of the economic gap between nations divided deeply historians, sociologists and economists as well. Dependencia theorists pointed exogenous causes for Latin American backwardness while the revisionists emphasized endogenous causes. Finished the Cold War and faced with new evidence, previous conclusions are far from being complete and final. There are different issues, which were superficially investigated, or they were sometimes entirely neglected. With the intention of transcending the two opposing currents of thought the present paper aims to synthetize all the accessible and collected data up today in Romania in order to analyze the impact of the markets' integration in the nineteenth century. On one hand, the Romanian nineteenth century economy is a fertile field for study, because it transferred neither slowly nor quickly from a “world economy” to another, which permitted a short relatively autonomous development. On other hand, even Romania was object to various studies in developmental economics, the foreign researchers did not access important evidence, which can change the conclusions on the main topic. The paper will present the economic and social parameters outlined in early 1800 and how these will evolve at the pressure of the Western markets. It will also point that the markets' integration generated two major trends as long-term tendencies: the increase of land price and the increase of the rate of interest. Both were impediment to a faster development of the Romanian society and in connection with other elements like the dysfunctionality of the state they will form a vicious circle of slow development.
Keywords: 330; markets' integration; periphery; Romania; land price; interest rate